Huawei Technologies Co. Ltd. / Muhammad Syafiq Naqiuddin Nil Amri - Nil Amri, Muhammad Syafiq Naqiuddin (2022)
This case study is about Huawei Technologies Co., Ltd., one of the famous technological companies nowadays that produces smartphones, televisions, refrigerators, and more. The products that this company has made are known worldwide because of the reputations and brand name. From this study, we can learn to analyze, apply the knowledge, reasoning, and concluding to understand this company. The first part of this case study focuses on collecting the company information such as the company's background, the problem statement and the purpose of the study. Through the analysis, some problems could be identified in the company. These problems were studied, and some solutions and improvement were proposed to achieve a better-quality product that customers know from all around the globe. The second part of the case study focuses on its’ background, organizational structure, products and services, technology, business, marketing, and operational strategy. For the third part, we only use SWOT, the short form for strength, weaknesses, opportunities, and threats of this company's product or services and understand how the company works. The fourth part is for me to find the findings and discussion for this report of a case study about Huawei Technologies Co., Ltd. And for the last one is for the recommendation and improvement section.